Padfield on copyright for archivists and records managers. - Padfield, Timothy; Stobo, Victoria (Facet Publishing, 2025)
This comprehensive and fully updated manual outlines copyright law in the UK with special reference to materials relevant to archive and records collections such as maps, legal records, records of local authorities, records of churches and faiths, and most notably unpublished works. It also offers advice on rights in the electronic environment and the problems associated with rights clearance, as well as covering related areas such as moral rights and rights in databases.